Student Partnership and Peer-Led Learning: Applying the Ketso Method in Public Health Education - Quinn-Walker, Natalie; Mejia-Mejia, Ana (Innovations in Pedagogy and Technology, 2026)
This study investigates the pedagogical impact of partnership work through implementing Ketso workshops in a Master of Public Health program. The research explores the experiences of facilitators and alums who return to co-lead interactive sessions focused on developing systematic review protocols. By engaging these past students in peer-led workshops, the project aims to understand how their role as facilitators contributes to their academic growth, skill development, and professional identity. Using a qualitative, thematic analysis of focus group data, the study captures insights into how peer partnership enhances critical thinking, communication, and leadership skills. The workshops provided were to ensure a collaborative learning environment was developed for the participants to build their confidence and share their ideas on their research. Thus, fostering an inclusive and empowering environment for the students. Whereby they can learn from the previous cohort, the student partners. Findings indicate that student-led sessions strengthen peer learning and promote facilitator growth in confidence, leadership, and reflective practice. The study supports the value of peer partnerships as an effective pedagogical strategy in higher education. By analysing the student partners’ experience, it was established that they gained transferable skills, such as time management, problem solving, and felt they were able to support fellow students with their Ketso research project. These skills will then be beneficial for their future career. Overall, the study demonstrated that the student partners were adaptable to the student needs, demonstrating professionalism.